Laparoscopic resolution of Wünderlich syndrome as a primary treatment - Gastón López Fontana; Rodrigo López Fontana; Juan Manuel Guglielmi; Pedro Bellesty; José Daniel López Laur (Archives of Renal Diseases and Management - Peertechz Publications, 2023)
Background: Spontaneous Retroperitoneal Hemorrhage, named Wünderlich Syndrome (WS) is usually managed by emergency surgeons with a conventional laparotomy. The aim is to report a patient with WS successfully treated by a laparoscopic approach avoiding open surgery.  Methods: A 50-year-old female was diagnosed with WS hemodynamic instability and flank pain. After a normal CT scan that discarded visceral injuries and stabilized, the patient underwent a laparoscopic renal exploration.  Results: Laparoscopic approach was as standard transperitoneal renal access. Fortunately, the hematoma was within Gerota fascia meaning a non-complex surgery. Due to the high R.E.N.A.L. score, it was necessary to complete a radical nephrectomy. Surgical time was 120 minutes without perioperative complications and the renal unit was retrieved using a Pfannenstiel incision. Estimate blood loss was not quantified. Finally, the hospital stay was 24 hrs. Conclusion: Laparoscopic approach could be performed in selected patients with WS especially when are hemodynamic stabilized with no visceral injury associated. Immediately treatment could facilitate the procedure because it avoids adherences or fibrosis due to hematoma. Experience in the laparoscopic approach is necessary.